Bronchial reactivity in asthmatic adults with normal spirometric values. - Higenbottam, T (1983)
A comparison was made between airways obstruction produced by exercise. Hyperventilation of cold air, hyperventilation of room air, and inhalation of ultrasonically nebulised distilled water. Seven asthmatics with no airflow obstruction were studied together with seven normal controls. All four provocations produced comparable mean reductions in forced expired volume in one second in the asthmatic patients, but no reduction was obtained in the controls. Whereas exercise, hyperventilation of cold air, and hyperventilation of room air were associated with heat loss from airways, inhalation of nebulised distilled water was not. Inhalation of ultrasonically nebulised distilled water offers a simple additional diagnostic test for asthma. Changes in the osmolality of airway surface liquid may possibly be the common mechanism by which "fog" and hyperventilation produce bronchoconstruction.